Prevalence of thyroid dysfunction in patients with acute atrial fibrillation attended at a cardiology emergency room - Barbisan, Juarez Neuhaus; Fuchs, Flávio Danni; Schaan, Beatriz D’Agord (São Paulo Medical Journal, 2003)
CONTEXT: Atrial fibrillation occurs frequently in patients with thyrotoxicosis, while it has low prevalence in adults of the general population. The prevalence of thyroid dysfunction in subjects with atrial fibrillation is 0 to 24%, a wide variation that is attributed to the different methodologies applied. However, continuous use of amiodarone in patients with previous atrial fibrillation may interfere with these prevalence rates. OBJECTIVE: In this study, we present the prevalence of thyroid dysfunction in adult patients who presented at a cardiac emergency room with acute atrial fibrillation, using a sensitive thyroid-stimulating hormone (TSH) assay and triiodothyronine (T3) and thyroxine (T4) determination. TYPE OF STUDY: Cross-sectional study SETTING: Emergency room of a tertiary care facility. PARTICIPANTS: A total of 72 patients with atrial fibrillation who presented at the emergency room not more than 48 hours after its onset. PROCEDURES: A standardized questionnaire and 12- lead electrocardiogram were applied, and T3, T4 and TSH were determined. MAIN MEASUREMENTS: TSH, T3 and T4 determination. RESULTS: Among these patients, 16.6% had altered thyroid function tests: 6.9% had hyperthyroidism, 5.6% hypothyroidism and 4.2% had increased T4 levels, by means of amiodarone use. CONCLUSION: The high prevalence of thyroid dysfunction in our study, especially hyperthyroidism, suggests that routine thyroid testing with sensitive thyroid-stimulating hormone assay is required in patients with acute atrial fibrillation.